2016
DOI: 10.1016/j.pharep.2016.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Modification of 5-methoxy-N,N-dimethyltryptamine-induced hyperactivity by monoamine oxidase A inhibitor harmaline in mice and the underlying serotonergic mechanisms

Abstract: Background 5-Methoxy-N,N-dimethyltryptamine (5-MeO-DMT) and harmaline are indolealkylamine (IAA) drugs often abused together. Our recent studies have revealed the significant effects of co-administered harmaline, a monoamine oxidase inhibitor (MAOI), on 5-MeO-DMT pharmacokinetics and thermoregulation. This study was to delineate the impact of harmaline and 5-MeO-DMT on home-cage activity in mouse models, as well as the contribution of serotonin (5-HT) receptors. Methods Home-cage activities of individual ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 49 publications
1
13
0
1
Order By: Relevance
“…In terms of its pharmacological effects, 5-MeO-DMT is a potent, fast-acting, psychedelic substance (Ott, 2001a). In animal models, 5-MeO-DMT acts as a non-selective 5-HT agonist (Shen et al, 2011), active at both the 5-HT 1A and 5-HT 2A receptors (Jiang et al, 2016). 5-MeO-DMT appears to have a higher affinity for the 5-HT 1A receptor subtype (Spencer et al, 1987) and also inhibits the reuptake of 5-HT (Nagai et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of its pharmacological effects, 5-MeO-DMT is a potent, fast-acting, psychedelic substance (Ott, 2001a). In animal models, 5-MeO-DMT acts as a non-selective 5-HT agonist (Shen et al, 2011), active at both the 5-HT 1A and 5-HT 2A receptors (Jiang et al, 2016). 5-MeO-DMT appears to have a higher affinity for the 5-HT 1A receptor subtype (Spencer et al, 1987) and also inhibits the reuptake of 5-HT (Nagai et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Higher dose combinations of harmaline (5 or 15 mg/kg) and 5-MeO-DMT (10 mg/kg) are toxic to both genotypes of mice 27 , 31 , 39 (and unpublished data). Such dose combinations caused a rapid increase of CBT (15–75 min) to an extremely high level ( e.g.…”
Section: Resultsmentioning
confidence: 69%
“…It has been shown that MAOI harmaline significantly enhances 5-MeO-DMT–induced hallucinogenic effects and toxicity 21 , 24 , 25 , 26 . Recent studies also demonstrate the influence of harmaline on 5-MeO-DMT–elicited neuropharmacological effects in animal models including thermoregulation and behaviors 31 , 39 , 40 , 41 , 42 , 43 as well as 5-MeO-DMT pharmacokinetics 27 , 29 , 43 . In the present study, a mathematical PK/PD model, which consists of an IDR model with baseline behavior, the adaptive feedback mechanism of the biological system, the impact of stress caused by handling and injection, and mechanistic actions of serotonergic drugs in thermomodulation, was developed and validated to characterize the relationship between drug concentrations and modulation of CBT by harmaline and 5-MeO-DMT, administered alone or in combination.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, 5HT1A receptors have been related to the behavioral alterations caused by this drug, such as hypoactivity ( Krebs-Thomson et al, 2006 ). Studies with mice found that administration of 5-Meo-DMT and harmaline reduce locomotion, but the effect is abolished by the administration of 5HT1A antagonists ( Krebs-Thomson et al, 2006 ; Jiang et al, 2016 ). Moreover, serotonin and mainly dopamine can cross-regulate acetylcholine ( Jackson et al, 1988 ; DeBoer et al, 1996 ).…”
Section: Discussionmentioning
confidence: 99%